Democratisation beyond the Crisis of Liberalism, Bringing Civil Society within the State - Gianolla, Cristiano (2017)
Philosophers, sociologists and political scientists may analyse political crises by looking at the relationship between the liberal and democratic pillars of liberal-democratic regimes. Social questioning of representation (abstention, apathy and protest) is a democratic response to the failure of the liberal pillar to democratise access to political power, therefore, the crisis of liberalism. M. K. Gandhi developed an alternative theory based on intercultural perspectives and on local, ethical communities. Through Boaventura de Sousa Santos’ “epistemologies of the South”, this article analyses how Gandhi’s work can be mobilised to foster democratisation theory. The study contends that to overcome the crises, democratisation of the liberal pillar is both paramount and achievable with a new interplay of the state and civil society.